A Comparison of Associations Between Self-Reported and Device-Based Sedentary Behavior and Obesity Markers in Adults: A Multi-National Cross-Sectional Study. (October 2022) - Ferrari, Gerson; Herrera-Cuenca, Marianella; Zalcman Zimberg, Ioná; Guajardo, Viviana; Gómez, Georgina; Quesada, Dayana; Rigotti, Attilio; Yadira Cortés, Lilia; Yépez García, Martha; Pareja, Rossina G.; Peralta, Miguel; Marques, Adilson; et al.
The purpose of this study was to examine the associations between self-reported and device-based measures of sedentary behavior (SB) with obesity markers in adults from Latin American countries. Sitting time and total time spent in different SBs were self-reported using two different questionnaires. Accelerometers were used to assess total sedentary time. Body mass index, waist, and neck circumferences were assessed. The highest self-reported sitting time was in Argentina, the highest total time spent in different SBs was in Brazil and Costa Rica, and the highest device-based sedentary time was observed in Peru. Neither self-reported sitting time, total time spent in different SBs or device-based sedentary time were associated with body mass index. Device-based sedentary time was positively associated with waist circumference and self-reported sitting time was positively associated with neck circumference. Caution is warranted when comparing the associations of self-reported and device-based assessments of SB with anthropometric variables.